CDX2 Expression in Primary and Metastatic Prostatic Adenocarcinoma: A Retrospective Study. (28th October 2020) - Girardo`, C; Fakhri`, N; Khokhar, H; Jetly, R; Bhalla, R
Abstract: Introduction/Objective: CDX2 encodes a transcription factor expressed in the nuclei of intestinal epithelial cells. The CDX2 immunohistochemical stain has excellent diagnostic utility in the setting of carcinoma of unknown primary, especially in combination with cytokeratins 7 and 20. While the stain is fairly specific for intestinal origin, it is also expressed in tumors of other origins. Only rare case reports have described positivity for CDX2 in metastatic prostatic adenocarcinoma. Having experienced a diagnostic dilemma involving CDX2 positivity in metastatic prostate cancer, we decided to study the rate of positivity for CDX2 in primary and metastatic prostate carcinomas. A literature search revealed several immunoassay studies and case reports of CDX2 positivity in the primary and metastatic setting. Methods: Following IRB approval, a search of the electronic medical records was performed to identify prostatic adenocarcinoma diagnoses on prostatectomy and metastatic specimens. Formalin-fixed, paraffin embedded blocks were obtained. Unstained slides were cut at 4µm and the staining protocol for CDX2 from Cell Marque™ was performed. 109 cases were stained, including 88 prostatectomy and 21 metastatic specimens. Results: Of the 109 cases, 75 were negative for CDX2, including 19 of the 21 metastatic cases. Of the remaining 34 cases, 10 were strongly positive for CDX2, including two metastatic cases (clavicle and right iliac bone). The remaining 24 were identified as weakly positive (12 cases), focally positive (7 cases), weakly and focally positive (3 cases), or patchy positive (2 cases). Overall, 36.36% of prostatectomy specimens had tumors with some CDX2 positivity, compared to 9.52% of metastatic cases. The patient ages at diagnosis ranged from 44 to 84 years, with a median value of 59 years, and at metastasis ranged from 51 to 87 years, with a median age of 64. PSA ranged from 2.8 to 3564 at diagnosis (median 9) and undetectable to 2024 at metastasis (median 56). Conclusion: CDX2 is often positive to some degree in both benign and malignant prostates, and can present a diagnostic pitfall in the case of metastasis. Hence, CDX2 positivity does not exclude the diagnosis of prostate cancer in the evaluation of unknown primary. In our study, the number of metastatic cases studied was relatively low. Future studies with more cases could better quantify the positive rate for CDX2 in metastatic prostate adenocarcinoma.